A Proteomic Analysis of Seed Proteins Expressed in a Brassica Somatic Hybrid and its two Parental Species (Plant Tissue Culture and Biotechnology, 2014)
Cabbage (Brassica oleracea) is one of the worlds major vegetable crops. However, the cabbage plant cannot be readily vernalized and produce seed in the tropics, whereas Chinese cabbage (Brassica campestris) can be conveniently vernalized at the seed stage. Proteins from seeds of an IPSA cabbage-Chinese cabbage somatic hybrid showing both hybrid vigour and the seed-stage vernalization characteristic were analyzed and compared with those of its two parents.  1D gel analysis indicated some differential expression of the seed proteins. Furthermore,  in 2D, gel analysis, 13 differentially expressed protein spots were examined:  of these ten were found to belong to the cruciferin seed storage protein complex, two were unidentifiable (no MASCOT match), and one was identified as late embryogenesis Abundant (LEA)-like protein, and was present only in the cabbage parent. This LEA-like protein in cabbage seed could therefore be implicated in interfering with the vernalization process in the tropics. Plant Tissue Cult. & Biotech. 24(1): 11-26, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19187